The impact of the provision of public infrastructures on regional economic development in Germany - Helmut Seitz; Georg Licht (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
The present paper presents an analysis of the impact of public infrastructure capital on regional economic developments in Germany. After presenting some descriptive statistical data on the economies of the 11 regions in (West) Germany a simple theoretical model of a cost-minimizing firm is presented in which the stock of public capital is included as a proxy for public services provided to firms as a fixed unpaid factor of production. Duality theory is used to recover the productivity effects of public infrastructures by calculating the cost-saving effects that are associated with public services. It is shown that these cost-saving effects work their way through adjustments in the demand for private inputs. Using a translog cost 'function we present panel estimates for the 11 federal states of (West) Germany with labour, structures and equipment as private factors of production. The results strongly indicate that public capital formation encourages private investment. In addition, it is demonstrated empirically that with respect to private capital a distinction between structures and equipment is of crucial importance because the effects on the former are of far greater importance than the effects on the latter.
Keywords: E6; H3; H4; 330; Regionale Entwicklung; Infrastrukturinvestition; Deutschland